Surgical Results of Sub-Axial Cervical Injury in Adult Patients Treated Via Anterior Approach - Faizullah Khan, Sajjad Ali, Saima Sheikh, Abdul Waheed, Sajid Khan, Akramullah, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To determine the results of treatment of sub-axial cervical injury in adults using open reduction, anterior approach and injury stabilization <72 hours. Place and Duration: In the Neurosurgery department of Pakistan Institute of Medical Sciences, Islamabad for one-year duration from January 2021 to December 2021. Methods: 82 total patients diagnosed with history of traumatic sub-axial injury using MRI and anteroposterior and x-rays lateral and anteroposterior views were selected. ASIA Impairment Scale was applied for valuation, which was completed at admission and 6-months later. Results: The patients mean age in this analysis was 39.20± 5.11 years. Conferring to the ASIA scale, 2 grades enhancement were realised in 24 cases and 54 cases have one grade improvement. Death occurred in 4 cases, 2 were linked to accompanying trauma, one was associated with the complication of the surgery, and the remaining 1 death were related to complications like aspiration. The results were good in 58 (74.5%) of 78 cases and satisfactory in 20 (25.5%). Conclusions: Anterior Cervical Discectomy and Fusion (ACDF) in this study showed good results and considered reliable option of treatment for improved stabilization of the spine anatomically with primary reduction.